2021
DOI: 10.1016/j.jvacx.2021.100089
|View full text |Cite
|
Sign up to set email alerts
|

The Leptospiral General Secretory Protein D (GspD), a secretin, elicits complement-independent bactericidal antibody against diverse Leptospira species and serovars

Abstract: Leptospirosis, the most common zoonotic infection worldwide, is a multi-system disorder affecting the kidney, liver, and lungs. Infections can be asymptomatic, self-limiting or progress to multi-organ system failure and pulmonary hemorrhage. The incidence of canine and human leptospirosis is steadily increasing worldwide. At least sixty-four Leptospira species and several hundred lipopolysaccharide-based serovars have been defined. Preventive vaccines are available for use in veterinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Towards our goal of constructing a chimeritope (chimeric epitope-based protein) vaccinogen for leptospirosis, we have sought to identify immunodominant epitope-containing domains of Leptospira proteins. In a previous study we identified the immunodominant bactericidal epitopes of the General secretory pathway D (GspD) protein [24] . The goal of this study was to identify the antigenic determinants of the Leptospira virulence factor, Loa22 ( Leptospira OmpA-like 22 kDa protein) [25] and assess its potential utility for inclusion in a multi-valent subunit vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Towards our goal of constructing a chimeritope (chimeric epitope-based protein) vaccinogen for leptospirosis, we have sought to identify immunodominant epitope-containing domains of Leptospira proteins. In a previous study we identified the immunodominant bactericidal epitopes of the General secretory pathway D (GspD) protein [24] . The goal of this study was to identify the antigenic determinants of the Leptospira virulence factor, Loa22 ( Leptospira OmpA-like 22 kDa protein) [25] and assess its potential utility for inclusion in a multi-valent subunit vaccine.…”
Section: Introductionmentioning
confidence: 99%